2018
DOI: 10.1038/s41431-018-0209-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of NDUFV1-dependent mitochondrial complex I deficiency

Abstract: Medical genomics research performed in diverse population facilitates a better understanding of the genetic basis of developmental disorders, with regional implications for community genetics. Autosomal recessive mitochondrial complex I deficiency (MCID) accounts for a constellation of clinical features, including encephalopathies, myopathies, and Leigh Syndrome. Using whole-exome sequencing, we identified biallelic missense variants in NDUFV1 that encodes the 51-kD subunit of complex I (NADH dehydrogenase) ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The value of 18.6±0.9 pmol FMN/mg of protein in intact brain mitochondria found in this study is almost equivalent to the values determined for the same preparation using acid extraction in our previous study (17)(18)(19)(20)(21) pmol FMN/mg of protein, ( 13)). The obtained value of complex I content in bovine SMP (70±6 pmol FMN/mg protein) is very close to the complex I content derived from 14 C-labeled piericidin A titer determined in the pioneering work of the Thomas Singer group (around 70 pmol/mg of protein) ( 52), but lower than the rotenone titer (110-200 pmol/mg protein) (53,54).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The value of 18.6±0.9 pmol FMN/mg of protein in intact brain mitochondria found in this study is almost equivalent to the values determined for the same preparation using acid extraction in our previous study (17)(18)(19)(20)(21) pmol FMN/mg of protein, ( 13)). The obtained value of complex I content in bovine SMP (70±6 pmol FMN/mg protein) is very close to the complex I content derived from 14 C-labeled piericidin A titer determined in the pioneering work of the Thomas Singer group (around 70 pmol/mg of protein) ( 52), but lower than the rotenone titer (110-200 pmol/mg protein) (53,54).…”
Section: Discussionsupporting
confidence: 89%
“…Impairments of complex I function at that first redox step are associated with several pathophysiological states and genetic diseases ( 14 ). Several human pathological mutations are localized in the NDUFV1 subunit close to the nucleotide-binding site and most likely can affect FMN redox properties, binding affinity, or stability of the enzyme ( 15 , 16 , 17 , 18 ). Loss of mitochondrial complex I integrity and activity was found in tissues of patients with Parkinson's disease ( 19 , 20 ), which plays a role in epileptogenesis ( 21 ).…”
mentioning
confidence: 99%
“…(Chen et al, 2018), andTFAM (Poh-joism€ aki et al, 2006). Still others, such as ABAT (Besse et al, 2015), FOXRED1 (Fassone et al, 2010), and NDUFV1 (Srivastava et al, 2018), have human homologs whose role in mitochondrial rare diseases has been documented. Several of the genes in this cluster have been implicated as important trait or disease markers in dairy cows, pigs, and sheep, making the predicted interactors of these genes of particular interest.…”
Section: Articlementioning
confidence: 99%
“…Previous work showed that cellular stress, which occurs during ischemia-reperfusion or early-onset preeclampsia, triggers the degradation of the NDUFV1 subunit (37,69); whereas protective strategies such as ischemia postconditioning can prevent NDUFV1 degradation (8). Moreover, genetic defects in NDUFV1 have been implicated in oxidative stress and mitochondrial diseases (56), suggesting the importance of this subunit in REDOX and bioenergetic homeostasis. Therefore, maintenance of NDUFV1 levels could constitute a therapeutic mechanism for preventing ROS-mediated cellular damage (Fig.…”
mentioning
confidence: 99%